THE INFLUENCE OF CORPORATE GOVERNANCE AND OWNERSHİP STRUCTURE ON FİRM PERFORMANCE: FAMİLY VS. NON-FAMİLY FİRMS REGİSTERED İN INDONESİA STOCK EXCHANGE - Ivone Ivone; Meiga Putri Antoni Ang (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Corporate governance, especially the distinctive of the board of directors owned by family firms, is contrast from non-family firms. A family company is a company where in its activities there is family involvement in company management decisions and the involvement of family members in board positions. The differences placed on the distinctive of the board of directors are expected to deploy as companion roles and counselling differently, so that the level of differentiation of the board can be defined in a diversity of characteristics in the category of gender and independent directors that will ultimately affect the firm’s performance. Family firms have characteristics in their ownership that show a different concentration impact on the firm’s performance when it’s in comparison to non-family companies. Therefore, this purpose of study is to analyse the influence of corporate governance and ownership structure among family firms and non-family firms on Companies recorded on the Indonesia Stock Exchange (IDX) in the period 2016-2020. This research technique uses panel regression results and test results using F test results, t tests, and coefficients of determination. This research technique uses panel regression results and test results using F test results, t tests, and coefficients of determination. The results showed that women's involvement had no significant effect on firm performance across the company, but had a significant negative effect on the performance of family firms and had a positive effect on the performance of non-family companies, and in ROA measurements in corporate performance, family companies were superior. But in Tobin's Q measurements, non-family companies are superior.